The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5606/tgkdc.dergisi.2021.21951
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ultrasound-guided versus bronchoscopy-guided dilatational tracheostomy after median sternotomy: A case-control study

Abstract: Background: In this study, we aimed to compare ultrasoundguided versus bronchoscopy-guided percutaneous dilatational tracheostomy outcomes in critically ill adult patients undergoing a median sternotomy. Methods: Between January 2015 and December 2020, a total of 54 patients (17 males, 37 females; mean age: 54.9±13.1 years; range, 39 to 77 years) who underwent elective ultrasound- or bronchoscopy-guided percutaneous dilatational tracheostomy after a median sternotomy were included. We compared the ultrasound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Surgical tracheostomy has been widely used and was described to be easily performed also in difficult scenarios such as COVID-19 ICUs during the coronavirus pandemic [ 76 ]. Percutaneous techniques have been growing in popularity in the last 20 years, but their ability to improve relevant outcomes is still debated [ 77 , 78 ]. Finally, Molardi et al proposed a hybrid technique to reduce hemorrhagic and infectious complications, such as sternotomy wound infection, in cardiac surgery patients [ 75 ].…”
Section: Prolonged Ventilation and Tracheostomymentioning
confidence: 99%
“…Surgical tracheostomy has been widely used and was described to be easily performed also in difficult scenarios such as COVID-19 ICUs during the coronavirus pandemic [ 76 ]. Percutaneous techniques have been growing in popularity in the last 20 years, but their ability to improve relevant outcomes is still debated [ 77 , 78 ]. Finally, Molardi et al proposed a hybrid technique to reduce hemorrhagic and infectious complications, such as sternotomy wound infection, in cardiac surgery patients [ 75 ].…”
Section: Prolonged Ventilation and Tracheostomymentioning
confidence: 99%
“…sound during PDT (26). Another two trials comparing ultrasonography and bronchoscopy for PDT showed no significant difference in procedure time or complications (27,28). Furthermore, Klotz et al (29) mentioned that bronchoscopy may reduce the safety of the PDT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, intervention can only be based on anatomical signs. A review of the literature showed that there are studies comparing the use of anatomical landmarks, USG, or FOB during PDT in terms of safety, duration, or development of complications [11][12][13]. However, no study was found that focuses on evaluating the effect of the morphological structure of individuals on the PDT intervention location and complications.…”
Section: Introductionmentioning
confidence: 99%